Uma visão dinâmica de alguns teoremas geométricos clássicos via GeoGebra - Silva, Victoria Mazotti Rodrigues da (2022)
We present in this work formal demonstrations and dynamic views of some classical geometric theorems, such as the theorems of Pythagoras, Pascal, and Napoleon. In the dynamic views of these theorems, as well as of some loci, including the Fermat, Nagel, and Gergonne points, we use GeoGebra. We conclude that GeoGebra is an excellent tool for building dynamic approaches, enabling detailed investigations of the hypotheses and thesis of a geometric theorem.